2018
DOI: 10.3390/md16060178
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro Anti-Tumor Activity of Phycocyanin against Non-Small Cell Lung Cancer Cells

Abstract: Phycocyanin, a type of functional food colorant, is shown to have a potent anti-cancer property. Non-small cell lung cancer (NSCLC) is one of the most aggressive form of cancers with few effective therapeutic options. Previous studies have demonstrated that phycocyanin exerts a growth inhibitory effect on NSCLC A549 cells. However, its biological function and underlying regulatory mechanism on other cells still remain unknown. Here, we investigated the in vitro function of phycocyanin on three typical NSCLC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 51 publications
(63 reference statements)
2
50
0
Order By: Relevance
“…Recently, we found that continuous intragastric administration of PC significantly reduced the accumulation of ROS inside oocytes of D-galactoseinduced aging mice and improved their oocyte quality, increasing female fertility (Li et al, 2016). Moreover, increasing evidence indicates that PC promotes cell activity, eliminates free radicals, and improves organ function (Li et al, 2013;Hao et al, 2018), and has become widely used as a natural substance with antioxidant, neuro-protective, anti-inflammatory, and oxygen free-radical scavenging properties (Romay et al, 2003;Gupta et al, 2011;Fernández-Rojas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found that continuous intragastric administration of PC significantly reduced the accumulation of ROS inside oocytes of D-galactoseinduced aging mice and improved their oocyte quality, increasing female fertility (Li et al, 2016). Moreover, increasing evidence indicates that PC promotes cell activity, eliminates free radicals, and improves organ function (Li et al, 2013;Hao et al, 2018), and has become widely used as a natural substance with antioxidant, neuro-protective, anti-inflammatory, and oxygen free-radical scavenging properties (Romay et al, 2003;Gupta et al, 2011;Fernández-Rojas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several reported protocols concerning isolation and purification of C-PC from various cyanobacterial species, still purification of C-PC from Arthrospira (Spirulina) platensis has great value among researchers for its medical applications [15]. On the contrary to previously reported purification protocols, an improvement in A 620 /A 280 ratio was performed in the present study based on reduction of protein impurities in crude extract via combination of mild isolation and ammonium sulphate precipitation of C-PC [2].…”
Section: Discussionmentioning
confidence: 99%
“…The application of natural products for chemoprevention and therapy has been becoming a more and more important issue over the past three decades [ 19 , 20 , 21 ]. Several studies have shown that some marine-derived compounds possess biological activity and pharmacological effect in cancer models with little or no side effects [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%